Costly democracy peacebuilding and democratization after war - Zurcher, Christoph (Stanford University Press, 2013)
Peacebuilding is an interactive process that involves collaboration between peacebuilders and the victorious elites of a postwar society. The book offers comparative analyses of recent cases of peacebuilding to deepen understanding of postwar democratization and better explain why peacebuilding missions often bring peace-but seldom democracy-to war-torn countries.